(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
This prospective observational study was carried out in the Department of Obstetrics & Gynecology, Chittagong Medical College Hospital from May 2002 to April 2003. The objective of the study was to evaluate various aspects of ruptured uterus regarding etiology, identification of risk factors, types of surgery carried out, maternal mortalities & morbidities and fetal outcome. During the period, out of total 9643 hospital deliveries, 70 cases of ruptured uterus were admitted. This gives an incidence of ruptured uterus 1 in 137 deliveries. Most of the women ranged between 20-29 years of age, while almost all of them were multi parous with mean parity of 5.5. There were only 2 cases in primi gravida , 81% patient was not on any antenatal care. Most of them (81%) were illiterate and from low socioeconomic (87%) group of the community. The common etiological risk factors were Cephalo pelvic disproportion (67%) Shoulder presentation (21%) Abuse of oxytocic drugs (10%) Previous caesarean scar (16%) and Malhandling by dai (42%). Most of the patients gave the history of prolonged labor for more than 24 hours. Shock and sepsis were the prominent presenting features. In most cases, the rupture site was on the lower segment (51%) and in 78% cases, the tear was complete. Out of 68 patients, 33(48%) underwent subtotal hysterectomy, 19(31%) had repair and 14(20.5%) patient undergone total hysterectomy. (2.8%) patients expired after arrival at the hospital before any surgical intervention could be done. Out of 70 patients, 7 patients died giving the mortality rate10%. The fetal mortality rate was 87%.Uterine rupture still remains one of the major causes of maternal and newborn morbidity and mortality in Bangladesh. Promotion of skilled attendance at birth, use of family planning among those at high risk, avoiding injudicious use of oxytocics during labor, correct use of Partograph and preventing unnecessary c-sections are essential in reducing the occurrence of uterine rupture. JCMCTA 2016 ; 27 (1) : 17 - 22